EVALUASI PELAKSANAAN SUPERVISI TERHADAP PENDOKUMENTASIAN ASUHAN KEPERAWATAN DI RUANG IRNA II RSUD KABUPATEN LOMBOK UTARA - Alwan Wijaya; Ni made Sumartiyawati; Izam Awildan; Suhartiningsih Suhartiningsih (LPPM STIKES Mataram, 2025)
Introduction: Supervision is essential in nursing management to guide staff nurses in care delivery. Indonesian nurses identify key issues in documentation, including lack of supervision, limited competence, and inefficient practices that can lead to errors. These challenges underscore the need for structured, scheduled supervision to enhance documentation quality and accuracy. Objective: This study aims to explore the implementation of supervision in nursing care documentation within inpatient wards. Methods: A qualitative approach using in-depth interview techniques was employed to collect data, involving a total of four informants Results: The results of the qualitative study revealed several insights regarding the supervision process. According to some informants, the supervision begins with gathering the team, followed by completing a checklist, conducting a briefing, and performing an evaluation. Regarding the personnel responsible for supervision, several informants stated that the head of the nursing division and the head of the ward serve as supervisors. Some informants mentioned that the head of the nursing division conducts supervision once a month, while others reported that the head of the ward performs supervision during shift handovers or when problems arise. In terms of supervision targets, informants indicated that supervision focuses on direct subordinates, the use and completeness of equipment, and the execution of nursing tasks. The impact of supervision, as reported by some informants, includes improvements in the quality of nursing care documentation and increased discipline among staff nurses. Conclusion: The implementation of supervision plays a vital role in the process of nursing care documentation. From the supervision flow, the responsible personnel, to the frequency of supervision, all aspects must be carried out in a scheduled manner to ensure a positive impact on the quality of nursing care documentation.